2019
DOI: 10.1590/1678-4162-10677
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping, plasticity tests and nanotagging of stem cells derived from adipose tissue of wild rodent agouti (Dasyprocta prymnolopha)

Abstract: There is a growing interest in the study of unspecialized mesenchymal stem cells, for there are still some discussions about their in vitro behavior. Regenerative medicine is a science undergoing improvement which develops treatments as cell therapy using somatic stem cells. In several studies, adipose tissue is presented as a source of multipotent adult cells that has several advantages over other tissue sources. This study aimed to characterize and evaluate the tagging of mesenchymal stem cells from the agou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Similarly, necrosis rates of the RPCsu lineage were also lower than the apoptosis rates, at first passage, with elevation after the sixth day of cultivation. Similar results have been described [23,33,34]. The increase in these rates is probably due to exhaustion of the culture medium due to the large cellular confluence, inducing necrosis [33].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, necrosis rates of the RPCsu lineage were also lower than the apoptosis rates, at first passage, with elevation after the sixth day of cultivation. Similar results have been described [23,33,34]. The increase in these rates is probably due to exhaustion of the culture medium due to the large cellular confluence, inducing necrosis [33].…”
supporting
confidence: 85%
“…Nevertheless, MSCBMsu showed a logarithmic increase over nine days before showing a reduction in cell concentration (Figure 1). This characteristic is not uncommon among mesenchymal stem cell lines, and studies with bone marrow, adipose tissue, and dental pulp lineages have commonly demonstrated similar evidence [33][34][35]. This observation raises the possibility that this group of somatic stem cells may present relevant metabolic adaptability.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, WJ-MSCs showed a logarithmic increase over nine days, with no Plateau Phase display, before showing a reduction in cell concentration (Figure 2). This characteristic is not uncommon among mesenchymal stem cell lines, and studies with bone marrow, adipose tissue, and dental pulp lineages have commonly demonstrated similar evidence (Argôlo Neto et al 2016;Rocha et al 2019;Soares et al 2019). This observation raises the possibility that this group of somatic stem cells may present relevant metabolic adaptability.…”
Section: Discussionmentioning
confidence: 67%